2019
DOI: 10.31632/ijalsr.2019v02i01.005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Progressive Muscle Relaxation (Pmr) on Blood Pressure Among Patients With Hypertension

Abstract: In the late 20th century, heart disease and blood vessels, including hypertension are expected to be the leading cause of death developed and developing countries, so that prevention and handling efforts need to be done through both pharmacological and non-pharmacological therapies. Nonpharmacological therapies including lifestyle modification, stress management, and anxiety are the first steps that must be taken. One of the efforts to manage stress and anxiety that can be done is by progressive muscle relaxat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Another study also found that progressive muscle relaxation combined with other therapies have good effect on hypertension. (25) The Supportive Educative System is part of the Basic Nursing System as a nursing agency to help individuals fulfil self-care demands so that patients can perform self-care optimally. The educationaldevelopmental system is the most appropriate to help hypertensive patients improve self-care behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Another study also found that progressive muscle relaxation combined with other therapies have good effect on hypertension. (25) The Supportive Educative System is part of the Basic Nursing System as a nursing agency to help individuals fulfil self-care demands so that patients can perform self-care optimally. The educationaldevelopmental system is the most appropriate to help hypertensive patients improve self-care behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the women in this study were already menopausal, a condition that makes women more susceptible to hypertension, as it is related to increased blood pressure. Menopause decreases the hormone estrogen, which protects blood vessels from damage (Rosdiana & Cahyati, 2019), and the American College of Cardiology states that the decline of estrogen levels at menopause is the main trigger of hypertension in women (Zhao et al, 2018). Meanwhile one of the factors that can cause hypertension in men is smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been conducted worldwide concerning the effectiveness of relaxation according to Jacobson in order to treat EH. According to conclusions from these studies and later meta-analyses [17][18][19][20][21][22], it may be presumed that Jacobson's progressive relaxation technique is an effective non-pharmacological method of supporting patients with EH. The effectiveness of the use of relaxation according to Jacobson in women during pregnancy was also noted [23].…”
Section: Relaxationmentioning
confidence: 99%